Rancangan Sistem Aplikasi Penilaian Rapot Siswa Kelas IV Mi Attahiriyah II - Abdul Halim; Ridwan Efendi (Jurnal Media Infotama, 2023)
The purpose of the study was to assess students in terms of subjects at MI Attahiriyah II to be more effective and efficient in the data input process. There have been no errors in the calculation of student course scores. Document storage is more effective in order to make it easier for employees to input data on student learning scores at MI Attahiriyah II. From the results of the ongoing analysis, there are problems in terms of assessment of report cards such as the management of subject matter and the search and renewal of subject matter that is less effective and wastes a lot of time on this. With the existing problems the author makes an application for the report card assessment system at MI Attahiriyah II using desktop java programming which is intended both for students who need data quickly and efficiently such as material questions, grades and data for both students and teachers.